Metode Pembelajaran Pendidikan Agama Islam bagi Anak Berkebutuhan Khusus di SLB Negeri 1 Lombok Barat - Joharatun Nisa; Jumarim Jumarim; Abdulloh Fuadi (PALAPA, 2023)
An important component in learning is the method. The success or failure of a learning activity depends on the method used. Because it is the method that determines how the learning process is carried out in the classroom. The PAI learning method for ABK is a method used by PAI teachers in SLB so that the material presented is easy to understand and understand, so that SLB students can implement their understanding in everyday life. This study aims to identify and analyze the PAI learning method for children with special needs at SLB Negeri 1 Lombok Barat for the types of disabilities who are blind, deaf, mentally retarded and physically disabled. This research is a field research with a qualitative approach. Data collection was carried out using observation, interviews and documentation techniques. The research process lasted for almost 4 months with research subjects being PAI teachers, school principals, curriculum assistants, students with special needs and student guardians. The data analysis technique used is data collection, data condensation, data presentation and drawing conclusions. While the object of research is the learning method of Islamic religious education for Children with Special Needs in the types of disabilities who are Blind, Deaf, Mentally Disabled and Physically Disabled in SLB Negeri 1 West Lombok. The results showed that: the PAI learning method used by PAI teachers for the type of visual impairment is the lecture and question and answer method, the deaf class uses the lecture and demonstration method, the mentally retarded class uses the lecture method and the disabled class uses the lecture and question and answer method.